The global economic crisis: Towards syndrome-free recovery for Africa - Augustin Kwasi Fosu; Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper outlines the impact of the global economic crisis on Africa. Recovery requires coordinated and consistent efforts to assist individual countries in mitigating (reducing) the risk, coping with the impact, and reducing risk over the longer term. Care should be exercised to maintain and improve good governance, which is essential for African countries to avoid introducing various anti-growth policy syndromes into their economies. These could arise if responses to the crisis result in (i) further boom-bust cycles and flaming the historically high volatility of African growth, including inflation, (ii) another debt crisis, (iii) household engaging in adverse coping strategies with lasting impacts; (iv) reversal of gains made in opening up African economies and aid architecture.
Keywords: G01; F42; O11; O55; 330; Africa; least developed countries; global economic crisis; financial crisis; governance